Profiles of EQ-5D utility scores in the daily practice of Japanese patients with rheumatoid arthritis; Analysis of the IORRA database. Issue 1 (2nd January 2016) - Hoshi, Daisuke; Tanaka, Eiichi; Igarashi, Ataru; Inoue, Eisuke; Kobayashi, Akiko; Sugimoto, Naoki; Shidara, Kumi; Sato, Eri; Seto, Yohei; Nakajima, Ayako; Momohara, Shigeki; Taniguchi, Atsuo; et al.
Abstract : Objective. Along with the advances of newly developed medical therapies in rheumatoid arthritis (RA), the number of pharmacoeconomical issues has been paid attention rapidly. For cost–utility analysis and determination of quality-adjusted life years, measurement of the EuroQol 5-dimensional descriptive system (EQ-5D) is essential, and has been used in several clinical studies. However, EQ-5D utility measure in Japanese patients with RA, especially in daily practice has not been fully documented. We analyzed the distribution of EQ5D utility scores and investigated the relationship between other clinical measures based on our Institute of Rheumatology, Rheumatoid Arthritis (IORRA) database. Method. Among 5, 284 outpatients who participated in the IORRA cohort study on October 2007, data from 5, 043 patients who completed the EQ-5D questionnaire were cross-sectionally analyzed. EQ-5D scores in each subgroup for baseline feature such as gender, age, disease activity score 28 (DAS28), and Japanese version of health assessment questionnaire (J-HAQ) were evaluated. For the evaluation of variables that influenced EQ-5D score, the contribution of each variable was evaluated by ANOVA. Results. Average EQ-5D score was 0.76 in 5, 284 patients (84% females, average age: 59.0 years, average disease duration: 12.4 years) whose average DAS28 was 3.3 and average J-HAQ was 0.74. EQ-5D scores were highly correlated with J-HAQ and DAS28, and were significantly lower in females and rheumatoid factor-positive patients. Older age, longer disease duration, higher DAS28, and higher J-HAQ were also significantly associated with lower EQ-5D scores. In multivariate analysis, the factor that most strongly influenced EQ-5D was J-HAQ (57.6%), followed by pain visual analog score (VAS; 12.5%). Conclusion. This study clearly demonstrated the distribution of EQ-5D score in the daily practice of RA patients, and provides important information for the pharmacoeconomical studies in rheumatology.